Genealogies of the colonial present: the rediscovery of the local in conflict management interventions in Mindanao, the Southern Philippines. Issue 5 (2nd September 2016) - Adam, Jeroen
Abstract: This article argues that the current attention on indigenous institutions, and the 'local' more generally, in peace-building and conflict management bears similarities with colonial and post-colonial attempts at pacifying volatile borderlands. This will be illustrated through a historical case study of the Southern Philippine island of Mindanao, which has witnessed a recurring Muslim insurgency throughout different phases of its history. In an attempt to cope with these violent uprisings, both the American colonial authorities and the authoritarian Marcos regime, as well as a range of contemporary international NGOs, have endorsed traditional institutional avenues of informal mediation. The argument for the deployment of the local in state reconstruction and peace-building as propagated in current literature on hybrid peace should therefore be reframed as a reinvention of colonial governance techniques of indirect rule. It will hereby also be argued that the underlying rationale for this current deployment of local/traditional institutions of mediation and governance confirms and builds further upon a colonial framing of the non-Western other as incapable of modern, liberal democracy.